Towards a 2025 National Ocean Literacy Strategy: Current Status and Future Needs in Primary Education - Freitas, Cátia; Bellgrove, Alecia; Venzo, Paul; Francis, Prue (Frontiers in Marine Science, 2022)
Globally, ocean health has become critically compromised due to compounding negative human impacts. Marine science education can play a key role in raising collective understanding of the vulnerability of marine environments and the importance of their protection, and this may best begin with integration of ocean literacy in schools. Previous research shows that K-12 students worldwide have a limited understanding of the ocean. This lack of familiarity with the ocean has been linked to the absence of topics related to marine science in most national school curricula. Teachers are the ultimate arbiters deciding whether and how to include these topics in their classes. However, the extent to which marine science may be currently being taught in formal education is still unknown. We used the Australian public school system as a case study to investigate the marine science teaching practices of primary school teachers (Foundation – Grade 6), through an online survey. Our results indicate that while teachers value the importance of ocean education from a young age, most of them rarely or only occasionally cover marine science topics in their lessons. Teachers cited increased levels of marine science knowledge and a greater availability of ocean-related educational resources linked to the school curriculum as key areas for improvement in ocean education practices. This study highlights the importance of formal marine science education in primary education, along with the need for professional development opportunities for teachers.